Concise dictionary of business management - Statt, David A., 1942- (Routledge, 1999)
This second edition of The Concise Dictionary of Business Management has been completely revised and updated to reflect the changing world of work and new technology. It has been expanded to include many new terms and buzzwords such as: contracting out, telecommuting, occupational choice, glass ceiling, superwoman, electronic brainstorming, the internet and the virtual corporation. It is the ideal quick reference guide for students and professionals wanting to cut through the jargon of business and management. This second edition of The Concise Dictionary of Business Management has been completely revised and updated to reflect the changing world of work and new technology. It has been expanded to include many new terms and buzzwords such as: contracting out, telecommuting, occupational choice, glass ceiling, superwoman, electronic brainstorming, the internet and the virtual corporation. It is the ideal quick reference guide for students and professionals wanting to cut through the jargon of business and management.